Formation Control Algorithm for Multiple Mobile Robots BasedonFuzzy Mathematics (Informatica, 2024)
The formation of multiple mobile robots has problems such as unsmooth formationtrajectory tracking and large formation control errors. To solve these problems, a three closed-loopsliding mode formation control method is proposed, which can achieve stable three closed-loopcontrol systems from both linear and angular velocity directions. At the same time, fuzzy theory isintroduced to design a fuzzy sliding mode control model for multiple mobile robots, which canmake the gain switching more smooth, and solve the problem of unsmooth and interference intrajectory tracking. The results showed that the linear velocity fluctuation of the research designedmodel was controlled within 5 seconds, and the angular velocity fluctuation was controlled within1 second. The overall mean value of position control indicators was 17.08, which was smaller thanthe comparison model. The average value of the position speed comprehensive control index was2.8, which was smaller than the comparison model. The research and design model had highercontrol accuracy and more stable control effects, ensuring the efficient and high-quality executionof tasks by robots, and can provide a technical basis for the formation motion control of multiplemobile robots.